Multi-stakeholder processes for food systems transformation: Lessons from Honduras - Van Wissen, Denise; Bonilla Findji, Osana; Wiegel, Jenny (2024)
In the context of challenging dynamics that contribute to maintaining food systems on current unsustainable trajectories, combined efforts and mobilization of a wide range of key players are imperative to generate actionable, evidence-based knowledge products and methodologies that can inform and transform decision-making processes to enable food system transformation. Researchers discussing the pathways to food system transformation still focus essentially on what needs to be done, than on the way to achieve it. This study undertakes an examination of three distinct cases of Multi-Stakeholder Processes (MSPs) implemented in Honduras: i) the national Food System profile MSP, ii) the National Food System Dialogue MSP, and iii) the Tegucigalpa Milan Urban Food Policy Pact. The study analyzes the effective contribution of these MSPs to the support of food systems transformation delving into the manner in which these MSPs have contributed to the adoption of a food system approach, thereby supporting national and subnational efforts, as well as to the implementation of coordinated and collaborative actions. A qualitative methodology, accompanied by specific indicators, has been employed to address their compliance with best MSP principles, to identify MSPs' successes and challenges, and to provide recommendations for effective MSP’s contributions, both for Honduras and globally